1995
DOI: 10.1128/mcb.15.8.4453
|View full text |Cite
|
Sign up to set email alerts
|

The Structure and Function of P55PIK Reveal a New Regulatory Subunit for Phosphatidylinositol 3-Kinase

Abstract: Phosphatidylinositol 3-kinase (PI-3 kinase) is implicated in the regulation of diverse cellular processes, including insulin-stimulated glucose transport. PI-3 kinase is composed of a 110-kDa catalytic subunit and an 85-kDa regulatory subunit. Here, we describe p55 PIK , a new regulatory subunit that was isolated by screening expression libraries with tyrosine-phosphorylated insulin receptor substrate 1 (IRS-1). p55PIK is composed of a unique 30-residue NH 2 terminus followed by a proline-rich motif and two Sr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
194
0
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(202 citation statements)
references
References 67 publications
7
194
0
1
Order By: Relevance
“…The mouse speci®c p85b transcript is depicted as signal C and can be observed in all four NIH3T3 cell derived transfectants ( Figure 2b, lanes 7 ± 10). The size of the mouse p85b transcript matches with the data from Pons et al (1995).…”
Section: Resultssupporting
confidence: 72%
“…The mouse speci®c p85b transcript is depicted as signal C and can be observed in all four NIH3T3 cell derived transfectants ( Figure 2b, lanes 7 ± 10). The size of the mouse p85b transcript matches with the data from Pons et al (1995).…”
Section: Resultssupporting
confidence: 72%
“…Activation of PI 3Ј-kinase through association of the p85␣ subunit with IRS-1 is well established (22,(55)(56)(57)(58). Consistent with this ligand and JAK-dependent association of the p85␣ subunit of PI 3Ј-kinase with IRS-1 and PI 3Ј-kinase "activation" were observed here for IL-4, OSM, and less obviously IFN-␣ (Wellferon) (Fig.…”
Section: Discussionsupporting
confidence: 66%
“…In addition, we observed that changes in PI 3-kinase were present in all suicide subjects whether they were diagnosed with major depression or other psychiatric illnesses, which further suggests that these changes are related to suicide rather than some specific psychopathology. A number of studies have shown that all catalytic and regulatory isoforms of class IA PI 3-kinase, except p110d, are highly expressed in the central nervous system (Pons et al, 1995;Antonetti et al, 1996;Fruman et al, 1996;Inukai et al, 1997). When we examined the relative mRNA distribution of catalytic and regulatory subunit isoforms of PI 3-kinase, an interesting pattern of expression emerged in the human PFC and hippocampus.…”
Section: Discussionmentioning
confidence: 96%